Conventional and Non-Conventional Document Sources-Gutenberg-II-Challenge to Print Media - Rajagopalan, T. S.; Rajan, T. N. (Journal of Information and Knowledge, 1984)
Discusses the various knowledge communication channels. Presents a historical overview of the emergence of communication media-oral to electronic media. Also presents the intertwining nature of these media. In conclusion suggests that the third world countries will have to develop capabilities to handle the multimedia transfer of information.